Looking Beyond the Fenceline: Assessing Protection Gaps for the World's Rivers. Issue 4 (9th November 2016) - Abell, Robin; Lehner, Bernhard; Thieme, Michele; Linke, Simon
Abstract: Protected areas are a cornerstone strategy for terrestrial and increasingly marine biodiversity conservation, but their use for conserving inland waters has received comparatively scant attention. In 2010, the Convention on Biological Diversity (CBD) included a target of 17% protection for inland waters, yet there has been no meaningful way of measuring progress toward that target. Defining and evaluating "protection" is especially complicated for rivers because their integrity is intimately linked to impacts in their upstream catchments. A new generation of global hydrographic data now enables a high‐resolution, standardized assessment of how upland activities may be propagated downstream. Here, we develop and apply, globally, a river protection metric that integrates both local and upstream catchment protection. We found that "integrated" river protection is highly variable across geographies and river size classes and in most basins falls short of the 17% CBD target. Around the world, about 70% of river reaches (by length) have no protected areas in their upstream catchments, and only 11.1% (by length) achieve full integrated protection. The average level of integrated protection is 13.5% globally, yet the majority of the world's largest basins show averages below 10%. Within basins, gaps are particularly severe for larger rivers.